The health for hearts united dissemination Trial: Implementation costs to reduce cardiovascular risk in African Americans - Jon C. Mills; Jeffrey Harman; Pauline Muturi; Christina Davis; Iris Young-Clark; Penny Ralston (Public Health in Practice)
Objectives: We report on the implementation costs of disseminating Health for Hearts United (HH), a church-based intervention designed to reduce CVD in African Americans. Study design: Cost analysis from dissemination trial of the CVD risk reducing, HH Intervention. Methods: Total costs included materials purchased and labor hours contributed by the academic team to implement the intervention. Materials costs included supplies and printing calculated in total, as well as on a per-participant basis. Labor hours were tracked for each team member. Labor hours were further categorized by the phase of the intervention (Training, Planning & Coaching, Delivery & Recognition). Per-participant and per-church costs are reported as the cost measurement divided by the total health leaders that participated (reached). Results: A total of n = 168 out of 173 health leader participants were reached (97 %). Total program costs were $87,207.66. Total material costs were $13,308.00, while labor costs accounted for 85 % of the total program costs ($87,207.66) at $73,899.66. The Training Phase comprised the largest portion (74 %) of the total labor costs ($54,598.29). Total per-health leader participant reached cost were $519.09. Conclusions: In one of the first studies to report the costs of implementing a CVD risk reducing intervention among African Americans in a church setting, in partnership with a local academic institution, training was the main cost driver. Costs of implementing HH could be reduced by lowering hourly labor cost. Future research should examine costs associated with different methods of implementation (e.g., using more lay people).